The mediating role of cognitive test anxiety on the relationship between academic procrastination and subjective wellbeing and academic performance - Albulescu, Ion; Labar, Adrian-Vicenţiu; Manea, Adriana-Denisa; Stan, Cristian (Frontiers in Public Health, 2024)
Background: Promoting wellness as a predictor of sustainable development empowers schools to model healthy behavior. The multiple interactions in real and virtual environments that today's youth are subjected to force schools to explore effective educational strategies to provide a quality education for students and their families.Purpose: This study examines the relationship between academic procrastination, assessment anxiety, subjective well-being, and academic performance. Comment [A1]: Number of real participants who took part in the studio Comment [A2]: Percentage of female gender in the sample of subjects Comment [A3]: Specifying the test administration period Comment [A4]: The statistical analysis involved was introduced.The software used Significance/Discussions: As a result of theoretical and practical investigations, it emerges that joint action of educational actors is required in the generation of effective educational strategies for the prevention and control of procrastination and evaluation anxiety, given the fact that both a high level of procrastination as well as assessment anxiety lead to the decrease of students' well-being, to the registration of low academic performances. In the long term, disruptive behavior (procrastination and anxious behavior) could generate low social and professional performance, which is a research question for a future longitudinal study. Comment [A6]: Extension of the theoretical foundation of the study Comment [A7]: Expanding the introduction with new references Comment [A8]: Extension of the theoretical foundation of the study * -.187 ** -.051 ** [-.101, -.018] Academic performance -.082 -.133 * -.051 ** [-.100, -.018] Note: * p < .05; ** p < .01; results based on 5000 bootstrap samples; CIbias-corrected 95% confidence interval for the indirect effects